Long-Term Incentive Plans exemplified by WIG20 companies (Economic and Political Thought, 2017)
In order to be competitive in the market, a company must fight notonly for customers but also for the best employees available in the marketwho can ensure adequate competitive advantage. To attract and retain suchemployees, a company must provide them with high remuneration and a widerange of fringe benefits. These incentives, however, are expensive and do notguarantee that employees will not leave to join a competitive company, whichwill offer them better conditions of employment. For this reason, companiesare looking for new incentive systems that will retain the best employees ina given company. Such opportunities are provided by Long-Term IncentivePlans (LTIPs). Such plans are advantageous enough and it seems natural touse them in companies. The aim of this paper is to demonstrate the applicationof LTIPs in Polish public companies. To that end, the WIG20 companieshave been used. The paper also examines the extent to which LTIPs areoffered to members of the supervisory boards, measured by the share of theirLTIP benefits in their total remuneration.